Endogenous Entry and Growth of Firms with Heterogeneous Firms - Markus Thomas Münter (Review of Industrial Organization, 2023)
We analyze the impact of persistent cost heterogeneity of potential firms on free entry equilibria under a Cournot setting. We show that firm heterogeneity always reduces the number of firms in equilibrium, and that vertical and horizontal market growth have different effects on industry population and firm dynamics. Vertical market growth always promotes entry and growth of new firms, but heterogeneity weakens this effect. For horizontal market growth, we identify two growth regimes: incumbents dominate in large markets with significant heterogeneity, while new entrants grow faster in smaller markets with low heterogeneity. In contrast to existing research, we show that higher degrees of heterogeneity among potential firms reduces entry rates in both cases.
Keywords: L1; L11; L22; 330; Endogenous market structure; Heterogeneity; Number of firms; Entry rates; Growth of firms; Cournot-nash-equilibria